The lord of the rings : the mythology of power - Chance, Jane, 1945- (University Press of Kentucky, 2001)
"With New Line Cinema's production of The Lord of the Rings film trilogy, the popularity of the works of J.R.R. Tolkien is unparalleled. Tolkien's books continue to be bestsellers decades after their original publication. An epic in league with those of Spenser and Malory, The Lord of the Rings trilogy, begun during Hitler's rise to power, celebrates the insignificant individual as hero in the modern world. Jane Chance's critical appraisal of Tolkien's heroic masterwork is the first to explore its "mythology of power"--That is, how power, politics, and language interact.